Übungen zur Statistik. - Schulze, Peter M. (De Gruyter Oldenbourg, 2014)
Students need intense practice in statistical methods to fully appreciate their diverse applications in the fields of economics and the social sciences. Together with the main textbook, the aim of this exercise book is to provide exercises in statistics for accompanying lectures, for study before and after lecture presentations, and for exam preparation.